Regional empowerment within the European framework : regionalist parties’ territory-oriented strategies in the regional, statewide and supranational parliamentary arenas - Strnad, Michal (2024)
This study addresses the parliamentary dimension of regional empowerment within the context of the European Union (EU). Focusing on regionalist parties as the principal political actors behind the regionalist agenda, it explores whether and how these parties advance territorial objectives in the parliaments they occupy. More specifically, it evaluates the legislation regionalist parties introduce in all direct representation organs within EU multi-level governance to empower the regional territory and community. Manual content analysis is applied to the territorial demands in the legislative proposals submitted by Südtiroler Freiheit, Femu a Corsica, and Plaid Cymry – distinct regionalist parties from different territorial settings – in the regional assemblies, statewide parliaments (lower and upper chamber), and the supranational Committee of the Regions and European Parliament over a recent salient, crisis-ridden period (January 2018 – December 2022). To validate and contextualise their legislative behaviour, a complementary framed thematic analysis is applied to their EU-related interventions in regional assemblies, i.e. on this party family’s core reference level, over the same timeframe. Regionalist parties adopt a proactive, context-sensitive, vertically coherent, and rule-abiding parliamentary strategy for regional empowerment. Proposing territoryoriented legislation on all territorial levels, they sharply differentiate what they demand from whom and where by modifying their territorial demands to fit the changing parliamentary context: Demands for greater self-government, safeguards against competence encroachments, and concrete region-oriented policies are addressed to the state from the regional assemblies and statewide parliaments.